2016
DOI: 10.1371/journal.pone.0168608
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Group CTX-M-9 Extended Spectrum Beta-Lactamases in Escherichia coli Isolates from Pediatric Patients in Mexico

Abstract: The aim of this study was to identify the presence of group CTX-M-9 extended spectrum beta-lactamases (ESBL) in clinical Escherichia coli isolates from pediatric patients. A total of 404 non-repeated positive ESBL E. coli isolates were collected from documented clinical infections in pediatric patients over a 2-year period. The identification and susceptibility profiles were determined using an automated system. Isolates that suggested ESBL production based on their resistance profiles to third and fourth gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…A notable example is the widespread CTX-M-9-group ESBL genes (e.g., bla CTX-M-9 , bla CTX-M-14 , bla CTX-M-27 ), which are the most common CTX-M genes circulating in Ent in some geographic regions [ 10 ]. A 2016 US study of the prevalence of CTX-M genes in Enterobacteriaceae found relative stability of bla CTX-M-15 in E. coli .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable example is the widespread CTX-M-9-group ESBL genes (e.g., bla CTX-M-9 , bla CTX-M-14 , bla CTX-M-27 ), which are the most common CTX-M genes circulating in Ent in some geographic regions [ 10 ]. A 2016 US study of the prevalence of CTX-M genes in Enterobacteriaceae found relative stability of bla CTX-M-15 in E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the clonal ST131 E. coli strains, CTX-M-9-group genes are associated with multiple strain types, and horizontal gene transfer via mobile genetic elements likely plays an important role in their dissemination [ 12 ]. While studies of ESBL-Ent in US children and internationally have reported infections due to CTX-M-9-group-producing Enterobacteriaceae (CTX-M-9-grp-Ent) [ 10 , 13 ], pediatric studies have not focused on the clinical and molecular epidemiology and impact of infections specifically due to CTX-M-9-grp-Ent.…”
Section: Introductionmentioning
confidence: 99%
“…pneumoniae and E . coli ) [ 3 ][ 27 , 28 ]. The CTX-M groups 2 and 8 have been reported in Asia, particularly in Salmonella species [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A notable example is the widespread CTX-M-9-group ESBL genes (e.g. blaCTX-M-9, blaCTX-M- 14, which are the most common CTX-M genes circulating in Ent in some geographic regions 10 . A 2016 U.S. study of prevalence of CTX-M genes in Enterobacteriaceae found relative stability of blaCTX-M-15 in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the clonal ST131 E. coli strains, CTX-M-9-group genes are associated with multiple strain types and horizontal gene transfer via mobile genetic elements likely plays an important role in their dissemination 12 . While studies of ESBL-Ent in U.S. children and internationally have reported infections due to CTX-M-9-group-producing Enterobacteriaceae (CTX-M-9-grp-Ent) 10,13 , pediatric studies have not focused on the clinical and molecular epidemiology and impact of infections specifically due to CTX-M-9-grp-Ent.…”
Section: Introductionmentioning
confidence: 99%